Tinjauan Fiqh Syafi‘iyyah Terhadap Legalitas Mahar Dari Uang Haram - Asnawi (Al-Mizan, 2021)
The dowry that must be given by a husband to his wife is the property he has or something of value, while the assets resulting from illicit business whose ownership is not clear, the legality of the dowry given is also unclear. Based on the above background, the author wishes to examine more deeply about the provisions of the dowry in marriage according to the view of al-Shafi'iyyah fiqh and the consequences if the husband pays the dowry with illicit assets. The goal to be achieved is to find out the provisions of the dowry in marriage according to the perspective of al-Shafi'iyyah fiqh and the law of paying the dowry of illicit assets and their consequences. This research was conducted in a qualitative research type with a descriptive approach. Based on the results of the study, it can be concluded that the position of the dowry in marriage according to al-Shafi'iyyah fiqh, is a reward for the benefits of a wife, which can be used as a dowry are goods that are legally traded, namely, holy, owned, and valuable, the mention of dowry in Marriage according to al-Shafi'iyyah fiqh perspective is circumcised, so marriage is valid even if the dowry is not mentioned in the contract, because something circumcised cannot affect the validity of a contract, because circumcision mentions the dowry in the contract for perfection. The law of paying dowry with illicit assets according to al-Shafi'iyyah fiqh is invalid, the consequences caused by paying dowry with illicit assets are that the husband is required to pay the dowry of the mitsil, if the illicit property that is used as the dowry has been determined in the contract by mentioning its characteristics or with isyarah, while if the dowry is not specified in the contract, but only mentions the type, then it must be replaced with lawful assets. The damage to the dowry mentioned in the contract cannot affect the continuity of the contract, because the dowry according to al-Shafi'iyyah fiqh is not part of the pillars of marriage.